Comparison of edible and leisure reinforcers. Issue 2 (17th April 2015) - Fahmie, Tara A.; Iwata, Brian A.; Jann, Kathryn E.
<x xml:space="preserve">Abstract</x> Results of previous research have shown that individuals with intellectual disabilities usually prefer edible items over leisure items. Other research has shown that sensory (leisure) items facilitate response acquisition and maintenance better than edible items do for individuals with autism. The current studies examined preference and performance for edible and leisure reinforcers by children with and without autism. Results showed that edible items were more preferred (Study 1) and resulted in higher rates of responding under maintenance conditions (Study 3) in subjects both with and without autism. Edible and leisure items resulted in similar rates of response acquisition (Study 2) for both samples and for subjects who showed different patterns of preference in Study 1.